Infrared Spectral Studies On Siddha Drug - Pavalaparpam - V.N. MEENA DEVI; P. NAGENDRA PRASAD; K. KALIRAJAN (International Journal of Pharma and Bio Sciences, 2010)
The traditional medicine is widely used for various human ailments in which plant and animal products are largely used for the drug preparation. In the Siddha medicine, Pavalaparpam is widely used for the treatment of indigestion, acidity, hyperacidity, ulcer and piles. It is used externally for various skin diseases and pimples. Pavalaparpam is a product which is taken in this present study for the standardization by using IR spectrum.